A CROSS SECTIONAL STUDY ON THE LEGAL NATURE OF INFORMED CONSENT FROM PATIENTS’S PERSPECTIVE - Mitra, Ankita; Sahoo, Dilip Kumar; Sahoo, Antaryami; Rath, Mahesh; Das, Sambit; Bharadwaj, Kasturi (Journal of Forensic Medicine and Toxicology, 2021)
In the field of health care, patient autonomy is a critical problem. It is common knowledge that patients’ understanding of legal and ethical problems surrounding the consent procedure is poor. As a result, the purpose of this study was to determine patient understanding, attitude, and views of the legal nature of informed consent. From